Steuerung globaler Arbeitsmigration von Gesundheitskräften Eine christlich-sozialethische Analyse des WHO-Verhaltenskodex - Damm, Hannah (Young Academics: Philosophie, 2023)
In this paper, Hannah Damm examines and assesses the WHO Code of Conduct on Global Migration from a Christian social ethical perspective. She uses the social ethical principles of personhood, solidarity, subsidiarity and sustainability as a yardstick. The analysis clearly shows the quality of the Code, but there are also weaknesses that can be traced back to its status as an international compromise paper. Therefore, from an ethical perspective, it needs to be refined in order to be able to offer recruiting countries, institutions or organisations a balanced guideline for action that makes the recruitment practices of global labour migration in the health sector ethically justifiable.